IMPLEMENTATION OF MOBILE COMMERCE OF PROCESSED SOYBEAN PRODUCTS TO INCREASE MSME MARKETING IN DADAPAN VILLAGE - Latifa Mutiara Zahra; Muhamad Muslihudin; Suyudi Suyudi (YHMM PUBLISHING, 2025)
This study aims to develop and analyze the implementation of an Android-based mobile commerce system for processed soybean products to enhance the competitiveness of SMEs in Dadapan Village. The research adopts the Waterfall Method approach, which includes analysis, design, implementation, and system testing stages. The developed system features product catalogs, shopping carts, and digital transaction capabilities with a responsive and user-friendly web commerce interface. System testing was conducted using black box and white box methods to ensure performance and reliability. In addition, user evaluation was carried out through questionnaires involving 45 respondents to assess user satisfaction levels. The results indicate that the implementation of mobile commerce significantly improves transaction efficiency, expands market reach, and increases consumer interest in soybean-based products. Most respondents expressed positive feedback regarding ease of use, access speed, and clarity of information provided by the application. Therefore, the developed system serves as an effective solution to support SME digitalization and strengthen the competitiveness of local products in the digital economy era.